2018
DOI: 10.1111/bjd.16270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-programmed cell death-1 immunotherapy for skin carcinomas and melanoma metastases in a patient with xeroderma pigmentosum

Abstract: Xeroderma pigmentosum (XP) is an orphan disease of poor prognosis. We report one case of parallel efficacy with anti-programmed cell death-1 (PD-1) antibody on both melanoma and skin carcinoma in a patient with XP. A 17-year-old patient presented with metastatic melanoma and multiple nonmelanoma skin cancers. He was treated with pembrolizumab, a monoclonal anti-PD-1 antibody, at a dose of 2 mg kg , every 3 weeks. Parallel therapeutic efficacy of anti-PD-1 was observed in metastatic melanoma and skin carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…Recently, antiprogrammed cell death-1 (PD-1) immunotherapy has shown efficacy against AS. 12 In addition, a recent report showed successful results in treating MM and nonmelanoma skin cancers with PD-1 inhibitor in patient with XP, 13 suggesting that PD-1 inhibitor can be considered as alternative therapy for AS in patients with XP who have difficulties in using radiotherapy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, antiprogrammed cell death-1 (PD-1) immunotherapy has shown efficacy against AS. 12 In addition, a recent report showed successful results in treating MM and nonmelanoma skin cancers with PD-1 inhibitor in patient with XP, 13 suggesting that PD-1 inhibitor can be considered as alternative therapy for AS in patients with XP who have difficulties in using radiotherapy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a rapid complete response after only three cycles was evidenced. Other reported cases of pembrolizumab in XP include, first of all Hauschild et al () (LE 4 following Oxford CEBM Levels of Evidence) subsequently Salomon et al () (LE 4 following Oxford CEBM Levels of Evidence) and they demonstrated a parallel therapeutic response of metastatic melanoma and primary cutaneous carcinomas. About adverse events, the most frequent are fatigue, rash, diarrhea, nausea or abdominal pain, and dysthyroidism.…”
Section: Introductionmentioning
confidence: 92%
“…Chirurgische Exzision ist die erste Wahl bei der Behandlung invasiver Hautkrebse, die aufgrund der Häufigkeit der benötigten Eingriffe so klein wie möglich erfolgen sollte [2]. Weitere Behandlungsmöglichkeiten beinhalten die topische Applikation von 5 %-iger Imiquimod-Creme, die ein schweres Erythem und Erosionen hervorrufen kann [15 -23], Cremes mit xenogenen Reparaturenzymen (Photolyase oder T4-Endonuklease) [24 -26], SMO-Inhibitoren [27,28], PD-1-Antikörper [29,30] und orale Retinoide [31,32]. [37].…”
Section: Introductionunclassified